2018
DOI: 10.1615/intjmedmushrooms.2018025833
|View full text |Cite
|
Sign up to set email alerts
|

Novel Kombucha Beverage from Lingzhi or Reishi Medicinal Mushroom, Ganoderma lucidum, with Antibacterial and Antioxidant Effects

Abstract: Kombucha is a nonalcoholic beverage traditionally made by fermenting black tea using a combination of yeast and acetic acid bacteria (AAB) cultures. Ganoderma lucidum hot water extract (HWE) was used-to our knowledge for the first time-to prepare a novel, health-promoting kombucha product. During the 11-day fermentation, pH, total acidity, and the numbers of yeasts and AAB were monitored. It was found that sweetened G. lucidum HWE was a good medium for yeast and AAB growth. The desired acidity for the beverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…In practice, however, there are comparatively few studies on the development of innovative macrofungus-based foods. Macrofungi are used in the production of kombucha (Sknepnek et al, 2018), beer (Leskosek-Cukalovic et al, 2010), and health wine.…”
Section: Macrofungal Food Product Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, however, there are comparatively few studies on the development of innovative macrofungus-based foods. Macrofungi are used in the production of kombucha (Sknepnek et al, 2018), beer (Leskosek-Cukalovic et al, 2010), and health wine.…”
Section: Macrofungal Food Product Developmentmentioning
confidence: 99%
“…As macrofungi are rich in umami components, they have appealing flavors and are ideal food flavoring agents. Nonvolatile and volatile compounds in shiitake extract could enhance cooked minced meat flavor (Sknepnek et al, 2018). The phenolic compounds in macrofungi have strong antioxidant and bacteriostatic activity and could, therefore, be applied in the food industry as natural antioxidants and antimicrobial agents (Bach et al, 2019).…”
Section: Macrofungal Food Product Developmentmentioning
confidence: 99%
“…31 These phenolic compounds are important antioxidants. 31,32 The major flavonoids with active antioxidant activity in ethanol extracts from G. lucidum were quercetin, myricetin and morin. 33 Recent studies have emphasized the importance of phenolic compounds as well as other bioactive components.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The extracts derived from medicinal Pleurotus species mushroom have been reported to have potential antibacterial and antifungal functions [37,38]. An invitro experiment was conducted by Sknepnek et al [39] with reishi mushroom (Ganoderma lucidum) on antimicrobial functions. Their studies concluded that the liquid Ganoderma lucidum mushroom beverage at a 0.04 mg/mL concentration was very useful against Staphylococcus epidermidis and Rhodococcus equi.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%